Citing the Scriptures in Paul's Letter to the Romans - Williams, Catrin H. (Svensk exegetisk årsbok, 2025)
This essay examines a range of issues concerning Paul's use of scriptural citations in his letter to the Romans. As well as discussing Paul's possible sources and citation practices, including techniques and strategies, the study considers audience-centred questions regarding the reception of Paul's 'use' of Scripture among his envisaged audiences.